Examining mean-volatility spillovers across national stock markets - Vinodh Kesavaraj Natarajan; Azariah Robert Raja Singh; Nagarajan Chidham Priya (Journal of Economics, Finance and Administrative Science, 2014)
The study of the stock market in a country and the understanding of the influence of stock market crashes within and across the markets has been the subject matter of many researches, academicians and analysts during recent times. In this study we investigate the mean-volatility spillover effects that happen across international stock markets. The study, by taking into consideration the stock market returns based on various indices, investigates the mean-volatility spillover effects using the GARCH in Mean model for the period January 2002 to December 2011. The GARCH-M model seeks to provide useful insights into how information is transmitted and disseminated across stock markets. In particular, the model examines the precise and separate measures of return spillovers and volatility spillovers. The analysis provides the evidence of strong mean and volatility spillover across some stock exchanges. – – El estudio del mercado de valores de un país y la comprensión de la influencia de los desplomes de la bolsa en y a través de los mercados ha sido el objeto de muchas investigaciones de académicos y analistas en los últimos tiempos. En este estudio se investigan los efectos de derrame de media volatilidad que se producen en los mercados de valores internacionales. El estudio, teniendo en cuenta la rentabilidad del mercado de valores basada en varios índices, investiga los efectos de derrame promedio de volatilidad utilizando el modelo GARCH en el período comprendido entre enero de 2002 y diciembre de 2011. El modelo GARCH-M pretende proporcionar ideas útiles sobre cómo se transmite y difunde la información a través de los mercados de valores. En particular, el modelo examina las medidas precisas y separadas de los efectos de excedentes de retorno y de volatilidad. El análisis proporciona la evidencia de una media y volatilidad fuertes a través de algunas bolsas de valores.
Keywords: A00; 330; Stock market index; Volatility; Spillovers; GARCH-M model; Índice de la bolsa de valores; Volatilidad; Derrames; Modelo GARCH-M